2020
DOI: 10.1038/s41598-020-71546-1
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of post-mortem central corneal thickness measurements using a portable optical coherence tomography system in humans: a prospective multicenter study

Abstract: To assess the repeatability and reproducibility of post-mortem central corneal thickness (CCT) measurements made by the portable iVue spectra-domain (SD) optical coherence tomography OCT (Optovue Inc, Fremont, CA) system in humans, and to prospectively establish the time-course of CCT after death. In a prospective multicenter setting, CCT measurements were obtained from 58 human eyes at the following 16 time-points after death: immediately (within 2 h), and at each hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Hopefully with further advances in HR-OCT platforms there will be automated settings for the anterior segment angiography scans and integrated software for reflectivity and vascular density assessment, which will significantly reduce the post-processing time and improve the applicability of this modality. Previous studies have shown good repeatability and reproducibility for measuring parameters such as central corneal thickness using HR-OCT [ 26 ]. However, as we aimed to explore the OCT characteristics of LSCD in this study, we did not look at the intra and interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully with further advances in HR-OCT platforms there will be automated settings for the anterior segment angiography scans and integrated software for reflectivity and vascular density assessment, which will significantly reduce the post-processing time and improve the applicability of this modality. Previous studies have shown good repeatability and reproducibility for measuring parameters such as central corneal thickness using HR-OCT [ 26 ]. However, as we aimed to explore the OCT characteristics of LSCD in this study, we did not look at the intra and interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Its portability in the supine position, plus the ability to record high-resolution scans for monitoring changes, and the ability for rapid and non-contact acquisition, make portable OCT imaging a valuable tool. 25 Trefoil-90 (G) and Trefoil-0 (H). The X-axis represents the mean of the readings recorded by both devices (device 1 + device 2/2), while the Y-axis represents the difference between the mean device 1 and device 2 readings (device 1 -device 2).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal transplantation has been proven to be the most effective therapy for corneal disorders such as opacity, keratoconus, corneal degeneration, scarring due to keratitis, trauma, and any physio-pathological changes on the ocular surface [1][2][3]. In addition to the appropriate examination of the characteristics of the donor and the tissue [4], immune privilege plays an important role in the success of corneal transplantation procedures [5,6].…”
Section: Introductionmentioning
confidence: 99%